The atlas maneuver eaudiobook - Berry, Steve (Cotton Malone, 2024)
From a celebrated New York Times bestselling author comes a Cotton Malone adventure in which Cotton unravels a mystery from World War II involving a legendary lost treasure known as Yamashita's Gold. 1945. In the waning months of World War II, Japan hid vast quantities of gold and other stolen valuables in boobytrapped underground caches all across the Philippines. By 1947 some of that loot was recovered, not by treasure hunters, but by the United States government, which told no one about the find. Instead, those assets were stamped classified, shipped to Europe, and secretly assimilated into something called the Black Eagle Trust. Retired Justice Department Operative Cotton Malone, is in Switzerland doing a favor for a friend. But what was supposed to be a simple operation turns violent and Cotton is thrust into a war between the world's oldest bank and the CIA. He quickly discovers that everything hinges on a woman from his past, who suddenly reappears harboring a host of explosive secrets. From the stolid banking halls of Luxembourg, to the secret vaults of Switzerland, and finally up into the treacherous mountains of southern Morocco, Cotton Malone is stymied at every turn–until he finally comes face-to-face with the Atlas Maneuver .